1972
DOI: 10.1246/bcsj.45.655
|View full text |Cite
|
Sign up to set email alerts
|

Butadiene Formation from Ethanol over Silica-Magnesia Catalysts

Abstract: Butadiene formation reaction from ethanol over various kinds of silica-magnesia having different MgO contents were studied from the standpoint of its acid-base catalysis. Maximum acidity was obtained at 50% MgO, while basicity increased with the MgO content. Silica-magnesia (85% MgO) having adequate acidity and basicity gave the maximum activity. The reaction mechanism and the roles of acidic and basic sites are discussed. The rate controlling step is the acetaldehyde formation catalyzed by basic sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 5 publications
5
87
0
Order By: Relevance
“…The decrease in the ethanol dehydration along with the increase in the ethanol dehydrogenation as the Mg:Si molar ratio was increased is in agreement with a reduction in the catalyst acidity, as expected when the Mg:Si increases. [10,18] On the other hand, interestingly, the effect of the Mg:Si molar ratio on 1,3-BD selectivity was different between MgO-SiO2 systems and MgO-SiO2 systems containing ZrO2 and ZnO. While a smooth rise in 1,3-BD selectivity was verified as the Mg:Si molar ratio increased for pure MgOSiO2 samples, Figure 1 (a), the same trend was not observed for catalysts containing ZrO 2 and ZnO, Figure 1 We have previously studied the effect of the Mg:Si molar ratio for Zn(II) and Zr(IV) containing MgO-SiO 2 systems, using the wet-kneading method in the MgO-SiO 2 preparation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in the ethanol dehydration along with the increase in the ethanol dehydrogenation as the Mg:Si molar ratio was increased is in agreement with a reduction in the catalyst acidity, as expected when the Mg:Si increases. [10,18] On the other hand, interestingly, the effect of the Mg:Si molar ratio on 1,3-BD selectivity was different between MgO-SiO2 systems and MgO-SiO2 systems containing ZrO2 and ZnO. While a smooth rise in 1,3-BD selectivity was verified as the Mg:Si molar ratio increased for pure MgOSiO2 samples, Figure 1 (a), the same trend was not observed for catalysts containing ZrO 2 and ZnO, Figure 1 We have previously studied the effect of the Mg:Si molar ratio for Zn(II) and Zr(IV) containing MgO-SiO 2 systems, using the wet-kneading method in the MgO-SiO 2 preparation.…”
Section: Resultsmentioning
confidence: 99%
“…[9] The route most widely accepted to account for 1,3-BD production from ethanol involves five consecutive reactions. [10][11][12][13][14][15][16] Initially, ethanol is dehydrogenated to acetaldehyde. Then, 3-hydroxybutanal is formed from acetaldehyde self-aldolisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of BD from ethanol. 5,15,23,30,31,47 acetaldol should be the possible intermediates related to the formation of BD. 23,24 In addition, acetaldehyde can be used as a reactant instead of ethanol.…”
Section: ¹1mentioning
confidence: 99%
“…Several studies revealed [6,7] that higher yield of BD was obtained from a feed of AL/EL mixture than from pure EL. Therefore, there is an obvious interest to get AL from the readily available EE.…”
Section: Introductionmentioning
confidence: 99%